Adventures with Cyanobacteria: A Personal Perspective - , Govindjee; Shevela, Dmitriy (Frontiers in Plant Science, 2011)
Cyanobacteria, or the blue-green algae as they used to be called until 1974, are the oldest oxygenic photosynthesizers. We summarize here adventures with them since the early 1960s. This includes studies on light absorption by cyanobacteria, excitation energy transfer at room temperature down to liquid helium temperature, fluorescence (kinetics as well as spectra) and its relationship to photosynthesis, and afterglow (or thermoluminescence) from them. Further, we summarize experiments on their two-light reaction - two-pigment system, as well as the unique role of bicarbonate (hydrogen carbonate) on the electron acceptor side of their photosystem II, PSII. This review, in addition, includes a discussion on the regulation of changes in phycobilins (mostly in PSII) and chlorophyll a (Chl a; mostly in photosystem I, PSI) under oscillating light, on the relationship of the slow fluorescence increase (the so-called S to M rise, especially in the presence of diuron) in minute time scale with the so-called state-changes, and on the possibility of limited oxygen evolution in mixotrophic PSI (minus) mutants, up to 30 minutes, in the presence of glucose. We end this review with a brief discussion on the position of cyanobacteria in the evolution of photosynthetic systems.